Genetic Structure of Cytochrome Oxidase Subunit II of Microcentrum rhombifolium - K, Mashhoor; R, Swathi; T, Leya; CvD, Sebastian; V.P., Akhilesh; D, Tanuja; P.A., Rosy; K V, Lazar (Research in Biotechnology, 2015)
The angle-wing katydid, Microcentrum rhombifolium is widely distributed in Asia-Pacific, Europe, Australia and America. Ã‚Â The molecular genetic structure of katydid fauna of Indian subcontinent is not studied in detail. Here we report the partial sequence of cytochrome oxidase subunit II (COII) gene of M. rhombifolium collected from Calicut of North Kerala and its phylogenetic position in the family Tettigonidae. Genetically M. rhombifolium is closure to Elimaea cheni isolated from China with 81% identity in nucleotide sequence. Conceptual translation of its peptide sequence showed 87% similarity to that of the katydid Kawanaphila yarraga. The partial sequence of COII of M. rhombifolium is deposited in Genbank (Genbank Accession Number. HM996893.1).